KAJIAN OPTIMASI JARINGAN GSM DI GEDUNG UTAMA UNIVERSITAS HKBP NOMMENSEN MEDAN - Sianturi, Libianko; Hutahuruk, Sindak (LPPM Universitas HKBP Nommensen, 2020)
Network optimization of the GSM - Global System for Mobile Communications aims to ensure the availability, integrity and reliability of such networks. In our study, we are measuring the quality of the signal to determine the condition of quality of signal especially at I and L buildings of Universitas HKBP Nommensen and the LOS (line of sight) conditions between the transceiver raiolink antenna. Based on analysis of the position of the transceiver radiolink antenna, data was obtained that the condition is eligible for Line of Sight (LOS). Based on the value of RxLevel, Rxqual and SQI measurements show that the third value of the parameters indicates better quality. But there are still some locations (rooms) on the 1st floor of building L and building I where the signal quality is slightly worse. To repair SQI in the room Level 1 building I and building L, it is recommended to evaluate and strengthen the power of the iBCMOS sistems that has been applied, especially the indoor antenna that serves on that floors.